Assessment and Analysis of Seismic Retrofitting Techniques for Performance-based Design of Steel Framed Building in Earthquake-prone Region - Yakubu, Abubakar Sadiq; Mishra, Nilesh B. (2024 International Conference on Communication, Computer Sciences and Engineering (IC3SE), 2024)
Steel bracing emerges as a good and notable approach for retrofitting, effectively reducing building displacement and strengthening the building. The bracing type used consist the Inverted V, X-Bracing and Diagonal bracing system. The study examines how earthquakes affect buildings, particularly the lateral forces they generate. Various bracing sections, such as Angle, Box, and Pipe sections, are employed to analyse and evaluate the forces in which the building initially fail to meet the required industry standard. A 7-storey steel building structure is used as the subject for retrofitting, the aim is to enhance its ability to withstand earthquakes. The retrofitting involves the use of three bracing systems: the Inverted V, X bracing, and Diagonal bracing. It includes a total of nine different models which are analysed, each with varied sections and bracing systems. Additionally, a model without any bracing is created for comparison. These models are analysed using Linear static analysis in ETABS software. After the comparison between the number of models, it becomes evident that the Box section outstands and performs better than the pipe section and the angle sections in tackling the lateral forces that occurred in the seismic region. It also assesses the effectiveness of the bracings in reducing storey displacement and demonstrating its effectiveness in enhancing the structural resilience.